2021
DOI: 10.1016/j.toxrep.2021.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-clinical assessment of safety, biodistribution and tumorigenicity of human mesenchymal stromal cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…No Alu DNA was detected in most tissues at the 4 weeks post-administration. 49 These results were consistent with those found with respect to Alu DNA detection in the lung up to 3 days post-inoculation in this study. Moreover, there was no Alu DNA detection in all tested tissues except the injection site (tail) 7 days post-administration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No Alu DNA was detected in most tissues at the 4 weeks post-administration. 49 These results were consistent with those found with respect to Alu DNA detection in the lung up to 3 days post-inoculation in this study. Moreover, there was no Alu DNA detection in all tested tissues except the injection site (tail) 7 days post-administration.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the previous study, which reported no tumorigenicity after inoculating BALB/c-nude mice with umbilical cord bloodderived MSCs. 48 Thäte et al 49 also reported that no MSCinduced tumors in immunodeficient NSG mice after repeat-dose I.V. injections at 4 × 10 7 cells/kg after a follow-up of 6 months, which was similar to data in this study.…”
Section: Sexsupporting
confidence: 90%
“…This result implies the safety and tolerability of MSC, which is in line with the recent studies using MSCs in animal models. 18,19 The therapeutic dose of BM-MSCs was conservatively set at a low dose (2.50×10 4 cells/head in mice, ∼1.25×10 6 cells/kg in humans) because damaged tissues with embolism and demyelination were observed in the medium-dose group (1.25×10 5 cells/head in mice, ∼6.25×10 6 cells/kg in humans). We also identified the biodistribution of BM-MSCs in a mouse model to evaluate the in vivo persistence of BM-MSCs in major organs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunodeficient mice are an increasingly popular research model due to their utility in studying human immune responses and cancer, and their use has increased significantly in preclinical research for multiple applications. 5,11,21,24,35,39,45,52 In preclinical studies in areas such as oncology and immunology, immunodeficient mice have been important to the understanding of mechanisms of disease, target identification and validation, and toxicologic effects of compounds. In addition, immunodeficient strains may recapitulate some of the immune dysfunction observed following immunosuppressive conditions in humans, such as chemotherapy, radiation therapy, surgery, infectious disease, or paraneoplastic syndromes, 17,48 and therefore may serve as a better predictor of toxicokinetics and safety in these instances.…”
Section: Introductionmentioning
confidence: 99%
“…33 In preclinical research, NSG mice have been used to test vaccine safety in the context of immunodeficient patients and the toxicity of human cell-based therapies. 24,45 Based on these research applications, NSG mice and other polygenic variants will likely continue to increase in popularity and value. However, immunodeficient mice created with multiple genetic mutations, including NSG mice, are very expensive to procure and often engrafted with tumors directly harvested from human patients and therefore irreplaceable.…”
Section: Introductionmentioning
confidence: 99%